Meteorological observations during POLARSTERN cruise PS126 - Holger Schmithüsen; Frank Otte; Julia Wenzel; Patrick Suter (PANGAEA, 2021)
The meteorological observatory Polarstern issues synoptical reports every 3 hours during times of ship operation. The reports are distritubed via global networks of the World Meteorological Organisation. When designated weather observers are onboard manual observations are included in the reports. For times that are not covered by an observer automatic reports are issued. All observations are made in compliance with standards of the World Meteorological Organisation and those of the German Weather Service (DWD). This dataset compiles all synoptical reports issued during Polarstern cruise PS126.
In: Schmithüsen, Holger; König-Langlo, Gert (2025): Meteorological observations during POLARSTERN cruises (ANT-I/1 et seq) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.987506